2011
DOI: 10.1002/dneu.20849
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal polarization: The cytoskeleton leads the way

Abstract: The morphology of cells is key to their function. Neurons extend a long axon and several shorter dendrites to transmit signals in the nervous system. This process of neuronal polarization is driven by the cytoskeleton. The first and decisive event during neuronal polarization is the specification of the axon. Distinct cytoskeletal dynamics and organization of the cytoskeleton determine the future axon while the other neurites become dendrites. Here, we will review how the cytoskeleton and its effectors drive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
133
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(137 citation statements)
references
References 148 publications
(185 reference statements)
2
133
2
Order By: Relevance
“…A similar mechanism is proposed to function in cortical and hippocampal neurons, which undergo a transitory multipolar stage during development, extending several undifferentiated neurites, one of which later becomes specified as the axon (Barnes and Polleux, 2009). In these neurons, the centrosome transiently localizes to the future axon site at the multipolar stage (Zmuda and Rivas, 1998;de Anda et al, 2005;de Anda et al, 2010) and polarization is accompanied by cytoskeletal remodeling and the segregation of numerous proteins, lipids and organelles (Arimura and Kaibuchi, 2007;Namba et al, 2011;Stiess and Bradke, 2011;Tahirovic and Bradke, 2009). Similar events are likely to be required for RB morphogenesis, which involves the formation of distinct central and peripheral axon compartments.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A similar mechanism is proposed to function in cortical and hippocampal neurons, which undergo a transitory multipolar stage during development, extending several undifferentiated neurites, one of which later becomes specified as the axon (Barnes and Polleux, 2009). In these neurons, the centrosome transiently localizes to the future axon site at the multipolar stage (Zmuda and Rivas, 1998;de Anda et al, 2005;de Anda et al, 2010) and polarization is accompanied by cytoskeletal remodeling and the segregation of numerous proteins, lipids and organelles (Arimura and Kaibuchi, 2007;Namba et al, 2011;Stiess and Bradke, 2011;Tahirovic and Bradke, 2009). Similar events are likely to be required for RB morphogenesis, which involves the formation of distinct central and peripheral axon compartments.…”
Section: Discussionmentioning
confidence: 79%
“…Axon formation is a key step of neuronal morphogenesis and the site of axon initiation is important for establishing correct neuronal polarity in vivo (Barnes and Polleux, 2009;Polleux and Snider, 2010). This process is regulated by mechanisms that establish asymmetry within the neuron and lead to localized remodeling of the F-actin and microtubule (MT) cytoskeleton within the nascent axon (Stiess and Bradke, 2011). When isolated and cultured at an early stage, many neurons are capable of undergoing polarization (Barnes and Polleux, 2009;Randlett et al, 2011a), demonstrating that cell typespecific intrinsic programs can direct axon formation in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, studies have mostly focused on the molecular mechanisms underlying the later stages of neuronal morphogenesis, including those mediating polarization [6][7][8][9], dendrite morphogenesis [10][11][12][13][14][15][16], synaptogenesis [17][18][19][20], and spinogenesis [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have identified molecules, such as collapsin response-mediated protein 2 (CRMP2), synapses of amphids defective (SAD) kinases, and glycogen synthase kinase-3β (GSK3β), that trigger axon specification independently of actin through microtubule dynamics Kishi et al, 2005;Yoshimura et al, 2005;Maniar et al, 2012). Furthermore, growing evidence from in vitro experiments suggests that microtubules do not merely act as simple building blocks or cargo tracks in this process, but may provide instructive signals for axon specification Witte et al, 2008;Stiess and Bradke, 2011). Interestingly, microtubule dynamics have also been implicated in axonal regeneration, indicating microtubules are important observed during development, we also demonstrate that axons of mec-7 animals display a reduced capacity for regeneration following laser-induced injury.…”
Section: Introductionsupporting
confidence: 56%
“…More recently, MTs themselves have been implicated as instructive cues in the process of axonal specification Stiess and Bradke, 2011;Witte et al, 2008). The transformation of a mature stable axon into a regrowing axon following injury requires changes to MT dynamics (reviewed in chapter 1).…”
Section: Developmental Control Of Axonal Morphology and Regenerationmentioning
confidence: 99%